Biopower, juridical power and the afterlife of rights: Medical assistance in dying and the Supreme Court of Canada - Young, Diana (Theoretical criminology, 2022)
This article considers how different modalities of power emerge in medical assistance in dying (MAID) cases, particularly with respect to the Supreme Court of Canada’s decision in Carter v. Canada (A.G.) [2015]. While juridical rationalities cast the issue of MAID in terms of individual rights, Carter and subsequent legislation distinguishes MAID from assisted suicide through the creation of a regulatory scheme, so that individuals seeking MAID continue to be governed by medical power. This may seem to confirm arguments that the image of subjectivity evoked by juridical discourses simply results in the reinforcement of existing power relations. However, this article argues that it is the very regulatory scheme governing MAID that provides points of resistance, giving the individual opportunities to challenge medical power in ways that may destabilize power relations.